Biological and molecular variability among PStV (peanut stripe virus) strains isolated from various peanut growing areas in Indonesia was studied based on their pathogenicity and coat protein genes. Six strains of PStV causing different types of symptoms on peanut leaves were used to study biological and molecular variability among these strains. Biological variability of the PStV strains was evaluated based on their pathogenicity on peanut cultivars, Gajah and Landak. While analysis of the coat - Hasriadi Mat Akin; Sudarsono Sudarsono; Rusmilah Suseno (Buletin Hama dan Penyakit Tumbuhan, 1999)
Biological and molecular variability among PStV (peanut stripe virus) strains isolated from various peanut growing areas in Indonesia was studied based on their pathogenicity and coat protein genes. Six strains of PStV causing different types of symptoms on peanut leaves were used to study biological and molecular variability among these strains. Biological variability of the PStV strains was evaluated based on their pathogenicity on peanut cultivars, Gajah and Landak. While analysis of the coat protein gene was used to study the molecular variability of PStV strains. Based on their pathogenicity, six PStV strains could be grouped into three groups, medium, strong, and very strong strains. Analysis of a coat protein gene showed the variability of the PStV strains were 0-2.1percent based on nucleotide sequence and 0-1.4percent based on predicted amino acid sequence. There was no correlation between biological and molecular variability.